Association between physical activity and risk of gastroesophageal reflux disease: A systematic review and meta-analysis - Chuting Yu; Tinglu Wang; Ye Gao; Yunfei Jiao; Huishan Jiang; Yan Bian; Wei Wang; Han Lin; Lei Xin; Luowei Wang (Elsevier, 2024)
Background: Lifestyle plays an important role in preventing and managing gastroesophageal reflux disease (GERD). In response to the conflicting results in previous studies, we performed a systematic review and meta-analysis to investigate this association. Methods: Relevant studies published until January 2023 were retrieved from 6 databases, and the prevalence of symptomatic gastroesophageal reflux (GER) or GERD was determined from the original studies. A random effects model was employed to meta-analyze the association by computing the pooled relative risk (RR) with 95% confidence intervals (95%CIs). Furthermore, subgroup and dose-response analyses were performed to explore subgroup differences and the association between cumulative physical activity (PA) time and GERD. Results: This meta-analysis included 33 studies comprising 242,850 participants. A significant negative association was observed between PA and the prevalence of symptomatic GER (RR = 0.74, 95%CI: 0.66-0.83; p < 0.01) or GERD (RR = 0.80, 95%CI: 0.76-0.84; p < 0.01), suggesting that engaging in PA might confer a protective benefit against GERD. Subgroup analyses consistently indicated the presence of this association across nearly all subgroups, particularly among the older individuals (RR<40 years:RR≥40 years = 0.85:0.69, p < 0.01) and smokers (RRsmoker:RRnon-smoker = 0.67:0.82, p = 0.03). Furthermore, a dose-response analysis revealed that individuals who engaged in 150 min of PA per week had a 72.09% lower risk of developing GERD. Conclusion: Maintaining high levels of PA decreased the risk of GERD, particularly among older adults and smokers. Meeting the recommended PA level of 150 min per week may significantly decrease the prevalence of GERD.